Diet and Neuroimaging Markers of Cerebrovascular Disease - Gu, Yian (2013)
Stroke is one of the leading causes of long-term disability and mortality. Mounting evidence from observational studies suggests that among lifestyle factors, diet may be playing an important role for the prevention of stroke. Neuroimaging markers, particularly white matter hyperintensity (WMH) volume and brain infarcts (BI) are more sensitive measurements of cerebrovascular disease than clinical assessments. We reviewed published observational and clinical studies that evaluate the association between dietary factors and WMH and BI. The few existing studies examined only a handful individual nutrients or foods (dietary intake of alcohol, B vitamins, fish, choline, serum markers of antioxidants, and a few food groups, Mediterranean-style diet, and nutrient biomarker patterns. Findings from these studies are inconclusive either due to conflicting results from different studies or due to lack of replication. Further studies are necessary to replicate the existing findings. Many other foods or nutrients or dietary patterns may worth of investigation and longitudinal studies are needed.